Signaling cascades of Pasteurella multocida toxin in immune evasion - Hieke-Kubatzky, Katharina; Handrick, Bianca; Hildebrand, Dagmar (Toxins, 2013)
Pasteurella multocida toxin (PMT) is a protein toxin found in toxigenic strains of Pasteurella multocida. PMT is the causative agent for atrophic rhinitis in pigs, a disease characterized by loss of nasal turbinate bones due to an inhibition of osteoblast function and an increase in osteoclast activity and numbers. Apart from this, PMT acts as a strong mitogen, protects from apoptosis and has an impact on the differentiation and function of immune cells. Many signaling pathways have been elucidated, however, the effect of these signaling cascades as a means to subvert the host’s immune system are just beginning to unravel.
Gesehen am 17.06.2021